Environmental Impact on Business Economy in Southeast Asia - Maharani, Adelia; Zulfikri, Ahmad; Amalina, Nur (SABA JAYA PUBLISHER, 2024)
Southeast Asia is experiencing rapid economic growth, driven by the manufacturing, services and agricultural sectors. Countries such as Vietnam and Indonesia stand out in global manufacturing, while Singapore and Malaysia excel in the services sector. However, structural challenges and dependence on natural resources in some countries mark differences in business situations. To achieve sustainable growth, investment in education, skills training, technology and infrastructure is necessary. Despite economic integration through free trade agreements and technology adoption, environmental challenges such as climate change, air and water pollution, and deforestation require collaboration between governments, companies and communities. Environmental protection and economic growth cannot be separated. Stakeholder collaboration is key to addressing environmental challenges and ensuring inclusive and sustainable economic growth. With joint efforts, the future of the business economy in Southeast Asia looks bright and full of potential.